X-ray reverberation in 1H 0707-495 revisited - Miller, L; Turner, T; Reeves, J; Braito, V (2010)
The narrow-line Seyfert 1 galaxy 1H 0707-495 has previously been identified as showing time lags between flux variations in the soft-energy (0.3-1 keV) and medium-energy (1-4 keV) X-ray bands that oscillate between positive and negative values as a function of the frequency of the mode of variation. Here we measure and analyse the lags also between a harder X-ray band (4-7.5 keV) and the soft and medium bands, using existing XMM-Newton data, and demonstrate that the entire spectrum of lags, considering both the full energy range, 0.3-7.5 keV, and the full frequency range, 10 -5≲ν≲ 10 -2 Hz, are inconsistent with previous claims of arising as reverberation associated with the inner accretion disc. Instead we demonstrate that a simple reverberation model, in which scattering or reflection is present in all X-ray bands, explains the full set of lags without requiring any ad hoc explanation for the time lag sign changes. The range of time delays required to explain the observed lags extends up to about 1800 s in the hard band. The results are consistent with reverberation caused by scattering of X-rays passing through an absorbing medium whose opacity decreases with increasing energy and that partially covers the source. A high covering factor of absorbing and scattering circumnuclear material is inferred. © 2010 The Authors. Journal compilation © 2010 RAS.